Cosmopolitan Capital and the Internationalization of the Field of Business Elites: Evidence from the Swiss Case. (June 2013) - Bühlmann, Felix; David, Thomas; Mach, André
The aim of this contribution is to explore how the recent internationalization and the increasing importance of 'cosmopolitan capital' has impacted on the structure and character of the field of the Swiss business elite. For this purpose we will develop the notion of cosmopolitan capital and comparatively investigate the field of the Swiss business elite in 1980, 2000 and 2010 with multiple correspondence analysis. We can show that in this period international managers with transnational careers and networks not only grow in number, but come to conquer the apex of the biggest and highest capitalized Swiss firms. At the same time, national forms of capital decline in importance and Swiss managers themselves are differentiated increasingly into national and international fractions.